Allopregnanolone decreases interictal spiking and fast ripples in an animal model of mesial temporal lobe epilepsy. (15th July 2017) - Lévesque, Maxime; Herrington, Rochelle; Leclerc, Leila; Rogawski, Michael A.; Avoli, Massimo
Abstract: The objective of this study was to characterize the impact of allopregnanolone, a neurosteroid that acts as a positive allosteric modulator of synaptic and extrasynaptic GABAA receptors, on interictal spikes and high-frequency oscillations (ripples: 80–200 Hz, fast ripples: 250–500 Hz) in the pilocarpine model of mesial temporal lobe epilepsy. Seven out of 25 Sprague-Dawley rats experiencing 1 h of pilocarpine-induced status epilepticus (SE) began treatment with allopregnanolone (9.6–12.8 mg/kg/day) on the following day. On day 4 after SE, video-depth EEG recordings from the hippocampal CA3 subfield and the entorhinal cortex were initiated and continued for 12 consecutive days. We found that 66.7% (12/18) of untreated animals exhibited seizures compared to 28.6% (2/7) of allopregnanolone-treated animals. Interictal spikes occurred less frequently in the CA3 subfield of allopregnanolone-treated rats (n = 4) than in untreated animals presenting (n = 4) or not presenting (n = 4) with spontaneous seizures (p < 0.05), and were less frequent in the entorhinal cortex compared to both untreated groups (p < 0.05). Finally, allopregnanolone-treated rats had significantly lower rates of interictal spikes with fast ripples (250–500 Hz) compared to untreated animals but only in CA3 (p < 0.05). Our findings show that allopregnanolone reduces the frequency of interictal spikes and fast ripples in CA3, a structure that plays an important role in ictogenesis and epileptogenesis. Neurosteroids may therefore influence pathological network activity leading to spontaneous seizures following pilocarpine-induced SE. Recordings after termination of allopregnanolone treatment will be however required to establish whether allopregnanolone exerts disease-modifying properties. Highlights: Allopregnanolone was administered continuously to pilocarpine-treated animals. Interictal spikes were less frequent in the CA3 subfield and entorhinal cortex. Fast ripples (250–500 Hz) were less frequent in the CA3 subfield. Neurosteroids may prevent the development of pathological activity.